The role of the ERK signaling pathway in promoting angiogenesis for treating ischemic diseases - Song, Yue-Yue; Liang, Dan; Liu, De-Kun; Lin, Lin; Zhang, Lei; Yang, Wen-Qing (Frontiers in Cell and Developmental Biology, 2023)
The main treatment strategy for ischemic diseases caused by conditions such as poor blood vessel formation or abnormal blood vessels, involves repairing the vascular damage and encouraging angiogenesis. One of the mitogen-activated protein kinase (MAPK) signaling pathways, the extracellular signal-regulated kinase (ERK) pathway, is followed by a tertiary enzymatic cascade of MAPKs that promotes angiogenesis, cell growth, and proliferation through a phosphorylation response. The mechanism by which ERK alleviates the ischemic state is not fully understood.Significant evidence suggests that the ERK signaling pathway plays a critical role in the occurrence and development of ischemic diseases. This review briefly describes the mechanisms underlying ERK-mediated angiogenesis in the treatment of ischemic diseases. Studies have shown that many drugs treat ischemic diseases by regulating the ERK signaling pathway to promote angiogenesis. The prospect of regulating the ERK signaling pathway in ischemic disorders is promising, and the development of drugs that specifically act on the ERK pathway may be a key target for promoting angiogenesis in the treatment of ischemic diseases.